Revisiting the Concept of Maqasid al-Sharia as a Moral Compass for Sustainable Social Development in Modern Muslim Societies - Abdurrahman Hilabi; Miftahul Ulum; Reni Puspita Sari (Harmony Philosophy: International Journal of Islamic Religious Studies and Sharia, 2025)
This study examines the integration of Maqasid al-Sharia the objectives of Islamic law into contemporary sustainable development frameworks, focusing on how Islamic ethical principles can guide social, economic, and environmental sustainability. Maqasid al-Sharia traditionally aims to preserve five core elements: religion, life, intellect, progeny, and wealth, all of which contribute to human well being. The research explores how these principles can be adapted to address modern challenges such as poverty, inequality, and environmental degradation, highlighting the potential of Maqasid al-Sharia to align with the United Nations Sustainable Development Goals (SDGs). Key Islamic principles, including justice (ʿadl), public welfare (maṣlaḥah), and ecological stewardship (khilafah), provide a moral framework for sustainable development, ensuring that economic growth is achieved alongside social justice and environmental preservation. The study also examines the role of Islamic finance, particularly tools like Sukuk, Zakat, and Waqf, in promoting sustainability by funding social welfare projects and supporting environmental initiatives. By comparing Maqasid al-Sharia with secular sustainability models, the research underscores the importance of integrating ethical and spiritual accountability into sustainability efforts. While secular models often prioritize economic growth, Islamic sustainability frameworks emphasize the interconnectedness of human development, social justice, and ecological balance, offering a more holistic approach. The findings suggest that integrating Maqasid al-Sharia into policy and development frameworks can provide a comprehensive, ethically grounded approach to addressing global sustainability challenges. Future research should focus on empirical studies to assess the practical application of Maqasid al-Sharia in real world sustainable development projects and policy making, particularly in Muslim majority societies.